Knowledge, Attitude, and Behavior of Farmers Towards Restoration of Degraded Land; the Cases of Harbo and Adea districts in the Oromia Region, Ethiopia - Hailu, Hiwot; Hinde, Omer; Midhakso, Rorisa; Bayera, Gizachaw; Limenih, Beliyu; Ayana, Alemayehu N (CV. Literasi Indonesia, 2024)
Land restoration is one of Ethiopia's top priorities for aligning development efforts with a climate-resilient green economy. In Ethiopia, initiatives to rehabilitate degraded land are generally evaluated in terms of the local people's economic and environmental impacts. Farmers' knowledge, attitudes, and actions toward land restoration, on the other hand, have to be taken into consideration for long-term natural resource conservation. As a consequence, this study examines the relationships between farmers' knowledge, attitude, and contributions to behavioral change in the restoration of degraded land. Data were collected from 120 farmers who participated in the restoration of degraded land. Structural equation models and mediation analyses were utilized for path analysis. The findings indicated that farmers had a good understanding of land restoration techniques. Analysis of the causal models revealed that farmers' attitude toward land restoration is highly influenced by their knowledge level of farmers. The outcome also revealed that positive attitudes of farmers resulted in behavioral change towards land restoration. Effective local community participation in the land restoration process and strengthening of their knowledge and attitudes that influence their behavior should be the cornerstones of sustainable land restoration.